The Icelandic Language at the Time of the Reformation - Veturliði Óskarsson (Nordlit: Tidsskrift i litteratur og kultur, 2019)
The process of the Reformation in Iceland in its narrow sense is framed by the publication of the New Testament in 1540 and the whole Bible in 1584. It is sometimes believed that Icelandic language would have changed more than what it has, if these translations had not seen the day.